Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2147/ijn.s59040
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous magnesium silicate-incorporated poly(ε-caprolactone)-poly(ethylene glycol)- poly(ε-caprolactone) bioactive composite beneficial to osteoblast behaviors

Abstract: Mesoporous magnesium silicate (m-MS) and poly(ε-caprolactone)-poly(ethylene glycol)-poly(ε-caprolactone) (PCL-PEG-PCL) composite (m-MPC) was synthesized by solvent casting method. The results suggest that the mechanical properties of compressive strength and elastic modulus, as well as hydrophilicity, of the m-MPC increased with increase of m-MS content in the composites. In addition, the weight loss of the m-MPC improved significantly with the increase of m-MS content during composite soaking in phosphate-buf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The presence of hydroxyl groups on the surface of DSTNs promotes interactions with water molecules, reducing the surface tension and making the nanofibers more prone to wetting, resulting in a lower WCA. 58 We also investigated surface functional groups and chemical interactions within the nanocomposite using FTIR spectroscopy, and the resulting FTIR spectra for various samples are depicted in Figure 3. In the FTIR spectrum of DSTNs, distinct peaks were identified at 463, 804, and 1100 cm −1 , signifying the bending, symmetric stretching, and asymmetric stretching vibrations of Si−O−Si bonds, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of hydroxyl groups on the surface of DSTNs promotes interactions with water molecules, reducing the surface tension and making the nanofibers more prone to wetting, resulting in a lower WCA. 58 We also investigated surface functional groups and chemical interactions within the nanocomposite using FTIR spectroscopy, and the resulting FTIR spectra for various samples are depicted in Figure 3. In the FTIR spectrum of DSTNs, distinct peaks were identified at 463, 804, and 1100 cm −1 , signifying the bending, symmetric stretching, and asymmetric stretching vibrations of Si−O−Si bonds, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This phenomenon is attributed to the inherent hydrophilic nature of silica-based materials. The presence of hydroxyl groups on the surface of DSTNs promotes interactions with water molecules, reducing the surface tension and making the nanofibers more prone to wetting, resulting in a lower WCA …”
Section: Resultsmentioning
confidence: 99%
“…There has been much research on degradable implants for applications in orthopedics ( 31 34 ), such as those made of polylactic-co-glycolic acid and magnesium alloys. It has been reported that the degradation of implant material and formation of new bone, and notably, the balance between these two processes, are important evaluation indices ( 35 ). Traditional methods of assessing degradation have unavoidable disadvantages, and the evaluation of new bone formation generally relies on images obtained from histology and radiography, which are imprecise and difficult to analyze quantitatively ( 36 , 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] In recent years, PEG was approved by U.S. Food and Drug Administration (FDA) for internal use in biomedical research and applications. 21 It has been used in bone tissue constructs for increasing hydrophilicity and degradability of the scaffolds [22][23][24] as well as to improve cellular attachment, guidance, and biocompatibility. [25][26][27] Various block copolymers of PEG with PCL have been used for different biomedical applications.…”
Section: Introductionmentioning
confidence: 99%